Prevalence of work related musculoskeletal disorders among load men in a market area in Kancheepuram district, Tamil Nadu - Vijayakarthikeyan, M.; Muthiah, Muthulakshmi; Angayarkanni, P. (International Journal Of Community Medicine And Public Health, 2021)
Background: Work related musculoskeletal disorders are globally responsible for deterioration in the quality of work, disability and distress among the workers. Load men are very much prone foe MSD due to longer hours of work, carrying heavy loads, improper rotation of work among the workers. Objectives of current study were to estimate the prevalence of WRMDs among load men, to identify the pattern of WRMDs among load men and to identify the comorbidities among load men. Methods: This is a cross-sectional analytical study conducted on occupational load men working in the market area in Padappai. Sample size included was 230 and data was collected using a prevalidated standardized Nordic questionnaire. Descriptive and analytical statistics were used to explain the study variables. Results: Prevalence of work related musculoskeletal disorder was 84% and 79% during the past 12 months and past 7 days respectively. WRMD prevalence during the past 12 months was highest in wrist/hand (78.3%) and hip/thigh (47.4%) during the past 12 months and past 7 days respectively. In this study, 57.4% had any form of comorbidity. Variables significantly associated with WRMD (p<0.05) were work experience, hours of work, weight of lift and climbing stairs in current study. Conclusions: The health issues of load men have been neglected and WRMD prevalence among load men was high in this study. Load men should undergo periodic health checkups and awareness about WRMDs must also be increased among them.